Systematic analysis of the dominant types of entomophages in fruit orchards - U.Rasulova; G.Turdiyeva; G.Rahmonova; R.Saliyeva; Rаkhmanova, М.К.; Khamdamov, К.Q. (Universitas Muhammadiyah Sidoarjo, 2019)
Abstract: The formation of entomophauna in orchards and their development has a great importance, and it greatly influences to the number of phitofags. During our observations of entomophages orchard in agrobiocenosis indentified 24 dominant types which belong to seven families. Moveover, researches of entomophages show 24 dominant types which belong to 7 families. Besides that we have analysed the share of entomophage varieties concerning the entomophages.